Literature and critical literacy pedagogy in the EFL classroom: Towards a model of teaching critical thinking skills - Bobkina, Jelena; Stefanova, Svetlana (Studies in Second Language Learning and Teaching, 2016)
Drawing on the numerous benefits of integrating literature in the EFL classroom, the present paper argues that the analysis of a fictional work in the process of foreign language acquisition offers a unique opportunity for students to explore, interpret, and understand the world around them. The paper presents strong evidence in favour of reader-centered critical reading as a means of encouraging observation and active evaluation not only of linguistic items, but also of a variety of meanings and viewpoints. The authors propose a model of teaching critical thinking skills focused on the reader’s response to a literary work. The practical application of the method, which adopts the critical literacy approach as a tool, is illustrated through a series of activities based on the poem “If” by Rudyard Kipling.